Mining-Ecological Footprint Nexus in the Global South: A Panel Data-Driven Approach - Baita, Abir; Erkut, Burak; Iscioglu, Deniz (Prague Univ Economics And Business, 2025)
This research investigates the environmental effects of mining activities in countries in the Global South, specifically focusing on Brazil, China, India, Indonesia and Pakistan, from 1990 to 2020. Utilizing advanced econometric techniques, especially panel data methods, the study identifies considerable variations in how key factors-such as mineral rents, forest areas, GDP per capita and freshwater resources-affect the ecological footprint. The results support the environmental Kuznets curve hypothesis and show that while mineral rents tend to decrease the ecological footprint, increased renewable freshwater resources are associated with a higher footprint (but the effect reverses in higher quantiles). No conclusive evidence can be found regarding the nexus between forest areas and the ecological footprint. By comparing the results with existing environmental standards and management practices, a significant gap between policy and practice is found, which contributes directly to the current environmental challenges and points out the need for country-specific strategies to increase environmental sustainability in the mining sector.
Keywords: Ecological footprint; environmental sustainability; mining activities; Global South